Beyond Technological Mediation: A Normative Practice Approach. - Boshuijzen-van Burken, Christine (Techné: Research in Philosophy & Technology, 2016)
Several philosophers of technology have argued that technology mediates human actions. For example, in the branch of post-phenomenology, authors such as Don Ihde and Peter-Paul Verbeek have described the mediating aspects of technology in terms of morality of technology (more prominent in Verbeek) as well as in the sense that technology changes our perception of ourselves and the world (more prominent in Ihde). In this article, different existing types of mediation are presented, critiqued, and enriched. The four types are illustrated by referring to military high-tech environments with a focus on visual data and imaging technologies. These technologies can mediate actions (1) by inviting certain behavior, (2) through amplification and reduction, (3) through built-in norms, and (4) through interpretation. The four types of mediation mainly focus on the technology or technological artifact itself. What these approaches fail to grasp, however, is the specific user practices in which most technologies function. In this article, it is argued that to understand the mediating aspects of technology more fully, attention should be paid to the specific user context in which the technology functions. Therefore, an enriched understanding of the four types of mediation of technology is proposed by taking the lens of normative practices and analyzing the different types of mediation through this lens. The Kunduz Airstrike Incident, which took place in 2009 in Afghanistan, is a case in which a visual data sharing device called Rover played a prominent role. This case is used in this article to illustrate how technology mediates human actions in military practice.